Extracellular Matrix Stiffness Regulates DNA Methylation by PKCα‐Dependent Nuclear Transport of DNMT3L. Issue 16 (26th June 2021) - Zhao, Xin‐Bin; Chen, Yun‐Ping; Tan, Min; Zhao, Lan; Zhai, Yuan‐Yuan; Sun, Yan‐Ling; Gong, Yan; Feng, Xi‐Qiao; Du, Jing; Fan, Yu‐Bo
Abstract: Extracellular matrix (ECM) stiffness has profound effects on the regulation of cell functions. DNA methylation is an important epigenetic modification governing gene expression. However, the effects of ECM stiffness on DNA methylation remain elusive. Here, it is reported that DNA methylation is sensitive to ECM stiffness, with a global hypermethylation under stiff ECM condition in mouse embryonic stem cells (mESCs) and embryonic fibroblasts compared with soft ECM. Stiff ECM enhances DNA methylation of both promoters and gene bodies, especially the 5' promoter regions of pluripotent genes. The enhanced DNA methylation is functionally required for the loss of pluripotent gene expression in mESCs grown on stiff ECM. Further experiments reveal that the nuclear transport of DNA methyltransferase 3‐like (DNMT3L) is promoted by stiff ECM in a protein kinase C α (PKC α )‐dependent manner and DNMT3L can be binding to Nanog promoter regions during cell–ECM interactions. These findings unveil DNA methylation as a novel target for the mechanical sensing mechanism of ECM stiffness, which provides a conserved mechanism for gene expression regulation during cell–ECM interactions. Abstract : Extracellular matrix (ECM) stiffness has profound effects on the regulation of cell functions. Stiff ECM enhances DNA methylation of pluripotent genes by the nuclear transport of DNA methyltransferase 3‐like binding to Nanog promoter in mouse embryonic stem cells (mESCs). DNA methylation is a novel target for the mechanical sensing mechanism during mESCs–ECM interactions.